EFFECT OF MINERAL AND ORGANIC NUTRIENTS ON HOT PEPPER YIELD AND DIFFERENT SHOOT THICKNESS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
A field experiment was conducted in order to determine whether it is possible to grow hot pepper under organic farming conditions in the saline soil of the central zone of the Republic of Karakalpakstan. In it, the effect of mineral, organic fertilizers and biostimulant on the yield of hot pepper was studied in different basic numbers (33.0, 50.0 and 66.0 thousand units). 49.7-55.6 c/ha and 63.1 c/ha when using organic fertilizers at the rate of 40 and 60 t/ha and an additional 2 l/ha of biostimulant provided to receive. In this case, the high indicator is observed when the base number is 50,000 units.